2020
DOI: 10.1212/wnl.0000000000010103
|View full text |Cite
|
Sign up to set email alerts
|

Teaching NeuroImages: Transient cytotoxic edema in a child with a novel ATP1A2 mutation

Abstract: A seven-year-old boy with prior episodes of hemiplegia and family history of hemiplegic migraine presented with fevers, waxing and waning encephalopathy (lethargic and poorly interactive), and left-sided weakness persistent throughout his five-week hospitalization. Diagnostic testing revealed a suspected pathogenic mutation in ATP1A2 (c.2285G>C; p.Gly762Ala), a gene associated with a broad phenotypic spectrum encompassing familial hemiplegic migraine type two (FHM2) and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Our patients exhibited the clinical features of AHC. However, our patients are also distinguished from the majority of classic AHC patients by the late age of onset (typically < 18 months), the lack of recurrent dystonia, and autonomic nervous manifestations associated with seizures [11][12][13]. Abnormal brain MRI is uncommon for AHC but has been reported previously [5].…”
Section: Discussionmentioning
confidence: 61%
“…Our patients exhibited the clinical features of AHC. However, our patients are also distinguished from the majority of classic AHC patients by the late age of onset (typically < 18 months), the lack of recurrent dystonia, and autonomic nervous manifestations associated with seizures [11][12][13]. Abnormal brain MRI is uncommon for AHC but has been reported previously [5].…”
Section: Discussionmentioning
confidence: 61%
“…This case presented with a variety of phenotypes that included fever, vomiting, alternating hemiplegia, convulsions, drowsiness, aphasia, episodic headache, unilateral cerebral oedema and cognitive impairment. HM caused by mutations in the ATP1A2 gene has been reported [ 6 , 7 ]. However, it is rare to report so many symptoms that are recurrent and varied in a single child.…”
Section: Resultsmentioning
confidence: 99%
“…These core symptoms and characteristics were consistent with the diagnostic criteria of SHM [ 2 ]. It has been widely reported that HM can sometimes be accompanied by symptoms such as fever, convulsion, altered consciousness (drowsiness or even coma), and cognitive impairment, as well as cerebral oedema seen in head MRI [ 3 , 6 , 7 ]. All of these symptoms occurred in our patient.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, when considering ATP1A2 mutations, it may be necessary to consider FHM and alternating hemiplegia of childhood (AHC), as they may share the same pathological mechanisms ( 21 23 ). Diagnostic criteria for AHC include: (1) repeated episodes of hemiplegia of varying severity or duration, involving alternating sides or both sides of the body; (2) onset before 18 months of age; (3) presence of other paroxysmal clinical signs, such as dystonic posturing, choreoathetoid movements, tonic spells, nystagmus, and autonomic features; and (4) progressive cognitive and neurological decline over time ( 24 ).…”
Section: Discussionmentioning
confidence: 99%